Transformation of Suara Muhammadiyah: From Da’wah Media to Progressive Islamic Corporation - Sri Herwindya Baskara Wijaya; Pawito Pawito; Widodo Muktiyo; Andre Noevi Rahmanto (International Journal of Emerging Issues in Islamic Studies, 2025)
Suara Muhammadiyah is the oldest Islamic media outlet in Indonesia, having transformed a da’wah (Islamic preaching) medium into a business entity based on the values of Islam Berkemajuan (Progressive Islam). The sustainability of this religious media requires adaptive strategies to navigate industrial changes, particularly in responding to digitalization challenges and financial sustainability. This study aims to analyze the transformation process of Suara Muhammadiyah (SM) from the perspective of business strategy and the integration of da’wah values into business management. This study employs a qualitative research method with a case study approach. Data were collected through in-depth interviews with Suara Muhammadiyah’s management, document analysis, and direct observations of its media operations and business units. A thematic analysis technique was used to identify transformation patterns, while data triangulation was applied to enhance the validity of the findings. The results indicate that the transformation of Suara Muhammadiyah is driven by digitalization, business diversification, and organizational restructuring. To ensure operational sustainability, the media has expanded its business units to include publishing, retail, and logistics. However, challenges remain, particularly in maintaining a balance between da’wah and commercialization, as well as competing with digital-based media. This study is limited to a case study of Suara Muhammadiyah without comparisons to other religious media. Further research is needed to explore the effectiveness of business strategies employed by other Islamic media in addressing industry challenges. This study contributes to understanding religious media sustainability through an innovative Islamic economic approach.